Enteroscopy in diagnosis and treatment of small bowel bleeding: A Delphi expert consensus. Issue 1 (January 2023) - Sorge, Andrea; Elli, Luca; Rondonotti, Emanuele; Pennazio, Marco; Spada, Cristiano; Cadoni, Sergio; Cannizzaro, Renato; Calabrese, Carlo; de Franchis, Roberto; Girelli, Carlo Maria; Marmo, Riccardo; Riccioni, Maria Elena; et al.
Abstract: Background: Enteroscopy plays an important role in the management of small bowel bleeding. However, current guidelines are not specifically designed for small bowel bleeding and recommendations from different international societies do not always align. Consequently, there is heterogeneity in the definitions of clinical entities, clinical practice policies, and adherence to guidelines among clinicians. This represents an obstacle to providing the best patient care and to obtain homogeneous data for clinical research. Aims: The aims of the study were to establish a consensus on the definitions of bleeding entities and on the role of enteroscopy in the management of small bowel bleeding using a Delphi process. Methods: A core group of eight experts in enteroscopy identified five main topics of small bowel bleeding management and drafted statements on each topic. An expert panel of nine gastroenterologists participated in three rounds of the Delphi process, together with the core group. Results: A total of 33 statements were approved after three rounds of Delphi voting. Conclusion: This Delphi consensus proposes clear definitions and a unifying strategy to standardize the management of small bowel bleeding. Furthermore, it provides a useful guide in daily practice for both clinical and technical issues of enteroscopy.